The role of gut microbiota in metabolic health: A nutrition-based perspective - Tripti Tripath
Gut microbiota, a dynamic and intricate ecosystem in our intestine, plays a critical function in metabolic health by affecting nutrient metabolism, immune defense, and energy homeostasis. Dysbiosis, an imbalance in gut microbial communities, has been reliably associated with metabolic disorders like obesity, type 2 diabetes, and cardiovascular disease. The current body of evidence strongly underscores the powerful effects of dietary interventions in shaping gut microbiota composition and function. Fiber-rich, polyphenol, probiotic, and prebiotic diets are found to improve microbial diversity, stimulate beneficial bacteria, and optimize metabolic outcomes. High-fat and high-sugar diets, on the other hand, lead to gut dysbiosis and metabolic dysfunction. It is through recognizing the complex interactions between diet and gut microbiota that there lies potential for establishing targeted nutritional strategies for the prevention and management of metabolic disorders. From a public health point of view, encouraging gut-friendly eating habits may be an affordable and sustainable way to enhance metabolic health at the individual and population levels. More research is urgently required to tailor dietary advice according to gut microbiome profiling to maximize health benefits through precision nutrition.